1984
DOI: 10.1111/j.1365-2265.1984.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin and Postmenopausal Osteoporosis

Abstract: Fasting serum calcitonin levels were measured in 54 postmenopausal women who had for 10 years been taking part in a double blind trial to assess the effect of the synthetic oestrogen, mestranol, on postmenopausal bone loss. There were no differences in calcitonin levels between mestranol treated and placebo groups. Fifteen of the women were challenged with a calcium infusion to measure the secretory reserve of calcitonin. Oestrogen treatment did not increase the calcitonin response to calcium infusion. The thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 15 publications
4
8
0
Order By: Relevance
“…Moreover, a report of CT gene mutation in a young patient with osteoporosis also supports the idea that CT is important in maintaining bone mass (Alevizaki et al 1989). Although the correlation between CT plasma level and BMD remains unclear (Chesnut et al 1980;Leggate et al 1984;Prince et al 1989), we can speculate that a variation in the CT locus may be correlated to variations in the effect of CT in maintaining calcium homeostasis. For example, the CT secretory reaction to calcium infusion in osteoporotic women was reported to be lower than that in normal women (Taggart et al 1982).…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, a report of CT gene mutation in a young patient with osteoporosis also supports the idea that CT is important in maintaining bone mass (Alevizaki et al 1989). Although the correlation between CT plasma level and BMD remains unclear (Chesnut et al 1980;Leggate et al 1984;Prince et al 1989), we can speculate that a variation in the CT locus may be correlated to variations in the effect of CT in maintaining calcium homeostasis. For example, the CT secretory reaction to calcium infusion in osteoporotic women was reported to be lower than that in normal women (Taggart et al 1982).…”
Section: Discussionsupporting
confidence: 55%
“…We found that short term estrogen therapy did not increase basal or stimulated serum CT concentrations in postmenopausal women. Similarly, Lobo et al (18) and Selby et al (19) did not find any effect of a short term E 2 therapy on basal CT levels, and Leggate et al (20) found no increase in CT secretion after long term E 2 administration in peri-and postmenopausal women. However, as mentioned previously, others have found that estrogens stimulate CT secretion (4)(5)(6).…”
Section: Discussionmentioning
confidence: 93%
“…According to some authors, lack of endogenous steroids leads to decreased levels of circulating and stored calcitonin (Deftos et al 1981;Taggart, Chesnut, Ivey et al 1982) following an initial phase of calcitonin hypersécrétion (Pansini, Bettocchi, Bergamini et al 1984) and to a net reabsorption of bone minerals and osteoporosis (Nordin, Aaron, Speed & Crilly, 1981). Leggate, Farish, Fletcher et al (1984) and Tiegs, Body, Wahner et al (1985) have questioned these conclusions because they were not able to show changes in plasma calcitonin. Thus the whole problem must be reconsidered.…”
Section: Discussionmentioning
confidence: 94%